Biological control in leaf‐cutting ants, atta sexdens (Hymenoptera: Formicidae), using pathogenic fungi - Filho, Tarcísio Marcos Macedo Mota [UNESP]; Stefanelli, Luis Eduardo Pontes [UNESP]; Camargo, Roberto da Silva [UNESP]; de Matos, Carlos Alberto Oliveira [UNESP]; Forti, Luiz Carlos [UNESP] (FapUNIFESP (SciELO), 2021)
– Chemical control using toxic baits containing the active ingredient sulfluramid at 0.3% (w/w) is the main method for controlling leaf-cutting ants of the genera Atta and Acromyrmex. However, since 2009, when sulfluramid was included in Annex B of the Stockholm Convention on Persistent Organic Pollutants, there has been an intense search for new methods that are efficient in controlling these insects. Among said new methods, biological control using pathogenic fungi has shown promising results in laboratory conditions. The objective of this study, given the context presented, was to assess the potential of the fungi Beauveria bassiana and Trichoderma harzianum in controlling Atta sexdens. Colonies of A. sexdens were exposed to the fungi by means of formulated baits provided in a foraging chamber, or of suspensions sprayed on the fungus garden, and had their behavioral changes recorded for 21 days. For both formulations, concentrations of 10 and 20% (w/w) of the fungi being studied were used. The results allowed concluding that baits containing 10 and 20% (w/w) of the fungi B. bassiana and T. harzianum were not efficient in controlling colonies of A. sexdens. On the other hand, spraying suspensions of 20% (w/w) of B. bassiana and 10% and 20% (w/w) of T. harzianum was efficient and resulted in 100% mortality of the colonies 11, 9 and 7 days after application, respectively. These findings indicate that the fungi B. bassiana and T. harzianum are promising as agents for the control of A. sexdens colonies, when sprayed on the fungus garden, although there are still some challenges as to their use related to the development of technologies for the application of the pathogen.
Controle biológico em formigas cortadeiras, atta sexdens (Hymenoptera: formicidae), usando fungos patogênicos
Keywords: Attini; Beauveria bassiana; Trichoderma harzianu